Some Aspects Of The Nutritional Requirements And Management Of Lampam Jawa, Puntius Gonionotus (Bleeker), Broodstock - S.Pathmasothy, (1996)

(untitled)
The reproductive patterns, optimum level of protein and fat in the diets in regulating oocyte development and the carrying capacity of spent Puntius gonionotus brood stock in ponds were studied. In experiment 1, the culture of fish of the same age in 40 m2 earthen ponds with stocking rates of 2, 500, 5, 000, 10, 000 and 20, 000 fish/ha for a duration of 5 months resulted in establishing distinct populations of same age but of different sizes. Utilizing similar populations from 400 m2 ponds, macroscopic observations indicated that P. gonionotus attained first sexual maturation when 5 months old at a critical size of 190 g . Carcass analysis of the fish indicated that sexual maturation only occurs when an adult physiological profile is attained. The faster growing fish attained adult physiological profile much earlier than the slower growing fish.The second experiment determined the pattern of vitellogenesis and consecutive gonadal development of the spent broodstock in 40 m2 earthen ponds . The required 50 spent females in each of the four trial s were acquired by induce breeding all the fish simultaneously. GS1 increments from these trials indicated that the same female could be spawned every 5 weeks. Based on changes in the HS1 values, it indicated that the liver plays a major role in vitellogenesis and gonadal recrudescence which required 6 weeks. During this process, proximate analysis of the developing gonads indicated that, in terms of quantity, protein is required in the largest amount fol lowed by fat, carbohydrate and minerals. Carcass analysis of the fish during this period indicated that there was no mass transfer of nutrients from the somatic components to the gonads during vitellogenesis and gonadal recrudescence. This suggested that all nutrients required for vitellogenesis and gonadal recrudescence were acquired directly from feed consumed The third experiment on determination of protein requirement for oocyte development was conducted in 500-liter fiberglass tanks with 6 spent females per tank and 4 tanks or replicates to each treatment. The fish were fed ad libitum for a duration of 5 weeks using diets with variable protein levels of 17, 25 and 3 2 % with a constant 6 % fat level. Results indicated that 3 2 % protein was critical for both somatic as well as reproductive growth.